Karakter dan Konsep Pemimpin dalam Perspektif al-Qur’an - Mahyudin, Mahyudin (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2022)
Leadership is an absolute thing that is one of the various central themes in the Islamic perspective to achieve success. However, leadership which is a wash to draw closer and worship Allah SWT, is starting to shift from its essence. Therefore, this study tries to bring back the leader's characteristics and concepts from the Qur'anic perspective. In addition, this would reinforce the leader's characteristics and concepts so that they can be used as a reference in shaping the personality of an ideal leader. The results of this study indicate that leadership in the Qur'an is explained through at least five concepts, namely Khalifah, Imam or Imamah, Ulul 'Amri, Wali, and Malik. In terms of characteristics, a leader should imitate the character of the Prophet Muhammad, namely Shidq, Amanah, Tabligh, and Fathanah, with which the organization he leads can achieve success and blessings according to the expected goals.